Managing the technical risk of performance-based building structures - De Almeida, Nuno Marques; Sousa, Vitor; Alves Dias, Luís; Branco, Fernando A. (Journal of Civil Engineering and Management, 2015)
During the past decades, the construction industry has been gradually adhering to major conceptual approaches such as those of quality, performance and risk. This paper proposes a management framework that enables the joint application of these conceptual approaches throughout the various phases of building projects – a Risk-Managed Performance-Based Building (RM-PBB) framework. This framework is based on the policies, procedures and practices of initiatives that gather international consensus, including performance-based model codes and standards, internationally recognized management principles and guidelines, standardized requirements for different types of management systems and also agreed principles of conformity assessment and auditing. This paper presents a summary of the strategic and operational components of this RM-PBB management framework. It also shows the practical outreach of the proposed framework by providing an example of application of each component of the management framework to the specific engineering context of building structures. The example of application further shows how technical risks arising from performance-based building structures can be managed, so that an intended level of structural performance can be fulfilled throughout all stages of a building project.